On memory construction and fictionalization. - Ngoi, Guat Peng (Inter-Asia Cultural Studies, 2015)
As a response to Ashis Nandy's article about memory work, this article argues that memories are closely linked to recognition, identity and historical construction while closely connected with local discourse based on post-colonial experiences. In some cases, the construction of memory involves mythical images. The article also addresses the tension between history construction and fictionalization, trying to indicate that some forbidden memories, such as those about revolution, can be reconstructed in literary writing.